Biomaterials : a basic introduction - Chen, Qizhi, 1963-; Thouas, George (CRC Press, Taylor & Francis Group, 2015)
"Biomaterials is a multidisciplinary subject, involving materials science, engineering, cell biology, and medicine. This textbook therefore provides an appropriate balance between depth and broadness of coverage, sufficient to enable understanding of the most important concepts and principles at the right level by students from a wide academic spectrum. This project has been developed from extensive lecture notes created by Dr. Chen in the teaching of biomaterial at Monash U, since 2008."--Resumé vydavatele
Keywords: biokompatibilita; biologické materiály; biopolymery; bioinženýrství; biomedicínské inženýrství; implantáty; protetika; biocompatibility; biological materials; biopolymers; bioengineering; biomedical engineering; implants; prosthetics; monografie; monographs